Large Scale Calcium Imaging of the Cerebellar Vermis During Sensory Stimulus Unravels Two Response’s Components That Differ in Their Spatiotemporal Properties - Byk, Hananel; Huang, Guo-Jen; Iwakura, Yoichiro; Yarom, Yosef (Frontiers in Systems Neuroscience, 2019)
The well documented precision of the cerebellar sagittal organization is commonly used to compose a comprehensive view on principles of cerebellar function. However, the physiological manifestation of this organization is either limited to information derived from single unit recordings or from imaging of a small group of closely located neurons. Here we used large scale imaging to monitor calcium concentration changes in the entire vermal area of folia V and VI in anesthetized mice. We found that the response to a strong auditory input or electrical shock to the tail area is composed of an early and a late component that differ in their spatiotemporal properties. The early component occurs throughout the scanned area whereas the late component reflects synchronous activation of Purkinje cells located along symmetric parasagittal bands that correspond well to sagittal band 2+ (Sugihara and Shinoda, 2004). Similar organization was found in the rigorously disorganized cerebellum of Cxcr4 KO mice, suggesting that the sagittal organization is determined by the climbing fiber inputs to the cerebellar cortex. The responses for both stimuli are followed by a prolonged recovery period but the rate of recovery from auditory stimulus is much longer, reflecting a different site for the adapting process. We suggest that these sensory inputs, which are commonly used to evoke startle response, activate two sets of climbing fiber inputs that differ in their spatiotemporal properties and contribute to the motor organization and habituation of the startle response. Significance Statement: The ensemble activity of neurons in the brain is one of the current challenges of neuroscience. Here we use a fast and large-scale calcium imaging system to monitor ensemble activity in the cerebellar cortex following auditory stimuli or electric shocks to the tail. The system, which enables the detection of the response to a single trail, reveals the robustness of the functional organization of the olivo-cerebellar system in sagittal bands that is preserved in genetically induced disorganized cerebellar cortex. Furthermore, the response, which represents the activation of two sets of climbing fibers inputs, is followed by a prolonged recovery process that indicates the cerebellar involvement in startle response.